483 Partial Treatment as a Risk Factor in Up-Conversion of Type 1 dAVFs. (April 2023) - Walker, Erin; Srienc, Anja I.; Guniganti, Ridhima Rao; Brinjikji, Waleed; Chen, Ching-Jen; Abecassis, Isaac Josh; Levitt, Michael Robert; Durnford, Andrew; Polifka, Adam J.; Derdeyn, Colin P.; Samaniego, Edgar A.; Kwasnicki, Amanda M.; et al.
Abstract : INTRODUCTION: Type 1 dural arteriovenous fistulas (dAVFs) lack cortical venous drainage and occasionally necessitate intervention depending on patient symptoms. Up-conversion is the rare transformation of a dAVF to a higher-grade. Causes for up-conversion are unknown. We tested the hypothesis whether partial treatment of type 1 dAVFs increases their likelihood of up-conversion. METHODS: We used the multicenter Consortium for Dural Arteriovenous Fistula Outcomes Research (CONDOR) database to perform a retrospective analysis of all patients with type 1 dAVFs. Propensity score analysis was utilized to determine if partial treatment was an independent risk factor for up-conversion. A regression model identified secondary risks that contributed to up-conversion. RESULTS: 358 out of 1077 patients within the consortium had type 1 dAVFs. 12% of patients who were partially treated for a type 1 dAVF experienced an up-conversion, while less than 1% of patients who received no treatment experienced up-conversion, and 0% of patients who had a complete treatment of their dAVF experienced up-conversion. Higher proportions of tinnitus, bruits, and intracranial hemorrhage at initial presentation were found in patients who up-converted. The majority of up-converted dAVFs were located in the transverse-sigmoid sinus and all received embolization as part of their treatment. CONCLUSIONS: Partial treatment is an independent risk factor for up-conversion when compared to no treatment or complete treatment. In the partial treatment group, hemorrhage at inital presentation and use of embolization as a treament modality are factors that increase risk for up-conversion.